RETRACTED: The construction of Language Teacher Identity in Ghana: A case study - Joyce Anku (ELT Forum: Journal of English Language Teaching, 2024)
The article titled "The construction of Language Teacher Identity in Ghana: A case study", by Joyce Anku, which was published in ELT Forum: Journal of English Language Teaching, Volume 13, Issue 2, pages 93-108, has been retracted by the publisher. This retraction is due to significant errors in the data analysis that invalidate the conclusions of the article. The authors have been notified of this retraction. The publisher takes this action to uphold the integrity of the scientific record.